ARGUMENT IS WAR in Malay and French: A Perspective from Cognitive Linguistics: ("Perdebatan ialah Peperangan" dalam Bahasa Melayu dan Bahasa Perancis: Satu Perspektif dari Sisi Linguistik Kognitif) (Jurnal Bahasa, 2018)
This paper examines the formation of the conceptual metaphor ARGUMENT IS WAR in Malay and French. This conceptual metaphor is commonly associated with the use of arguments presented by the parties involved in a debating session. It will be viewed and reviewed in particular based on the improved elements in the conceptual metaphor theory such as the concepts of complex and primary metaphors. For this analysis, four linguistic metaphors have been chosen from two Malay novels and one French novel. In order to identify these linguistic metaphors, the metaphor identification procedure was used and two samples in Malay and two samples in French were selected. The findings show that ARGUMENT IS WAR is a complex metaphor formed through a number of primary metaphors that are basic and simple in nature. In addition, the metaphor was also detected as a cognitive process that occurs during the negotiation process. The study shows that the similarities and differences that can be discovered through mapping from the source domain to the target domain are the result of various factors such as manners and ethics, religion and philosophy of life.Keywords: complex metaphor, primary metaphor, Malay language, French language, similarities, differences